NAVIGATING TRUTH IN THE NEWS ENVIRONMENT ON DIGITAL PLATFORMS - Hadi, Ido Prijana; Lesmana, Fanny; Wijayanti, Chory Angela (Jurnal Visi Komunikasi, 2025)
Online media platforms, mainly social media and Google, are often referenced in the crowded digital information environment. However, this has led to increased violations such as ignoring ethical codes, lack of verification, unbalanced reporting, sexual provocation, and slanderous news. The urgency of this research is to find out the subject's experience when the quantity of information is abundant and whether they have balanced it with literacy in navigating to get the truth when consuming news on digital platforms. This study aims to discover and reveal how sceptical audiences experience navigating the truth in the news environment on digital platforms. Using a descriptive phenomenology approach, the qualitative research design was conducted through in-depth interviews with 14 participants from various work professions. The results found that actors who navigate the truth use social media applications such as YouTube, Instagram, Twitter, and Facebook by checking the credibility of news sources, considering context, and verifying from other sources. Users chose to wait for the original truth of the event through follow-up posts from multiple sources on WA, Line, and Snapchat. Moreover, search engines are used to confirm news on social media, such as the 2024 elections in Indonesia.